Simultaneous traumatic rupture of the patellar tendon and the contralateral quadriceps tendon in a healthy individual. (5th November 2010) - Kumar, S; Rachakatla, N; Kerin, C; Kumar, R
Abstract : A simultaneous traumatic complete rupture of the patellar tendon and the contralateral quadriceps tendon is reported to occur in patients with renal failure and other inflammatory diseases, but is extremely rare in a healthy individual because of the different contributory factors and mechanisms of injury. We present a rare case report of such a combination of injuries in a 48-year-old healthy man. To our knowledge only three such cases have been reported in the English literature. This is an unusual combination and hence there is potential for missed diagnosis leading to suboptimal treatment.